Urinary Trypsin Inhibitor Protects Tight Junctions of Septic Pulmonary Capillary Endothelial Cells by Regulating the Functions of Macrophages - Wang R; Song W; Xie C; Zhong W; Xu H; Zhou Q; Deng Y; Hong Y; Li X; Fang M (Dove Medical Press, 2021)
Ruijie Wang,1,2,* Wenliang Song,3,* Chengyuan Xie,2,4,* Wenhong Zhong,2 Hui Xu,2,5 Qiuping Zhou,1,2 Yiyu Deng,2 Yimei Hong,2 Xin Li,2 Ming Fang1,2 1Department of Intensive Care Unit, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, School of Medicine, South China University of Technology, Guangzhou, People’s Republic of China; 2Department of Emergency and Critical Care Medicine, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, People’s Republic of China; 3Department of Critical Care Medicine, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 4The Second School of Clinical Medicine, Southern Medical University, Guangzhou, People’s Republic of China; 5Shantou University Medical College, Shantou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming FangDepartment of Intensive Care Unit, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, School of Medicine, South China University of Technology, Guangzhou, 510080, People’s Republic of ChinaTel +8613527774075Email drfangming@163.comBackground: Our previous study found that urinary trypsin inhibitor (ulinastatin, UTI) protected tight junctions (TJs) of lung endothelia via TNF-α inhibition, thereby alleviating pulmonary capillary permeability in septic rats. As the activated macrophage is the main source of TNF-α in sepsis, we speculate that UTI may exert the above effects by regulating the functions of macrophages.Methods: Bone-marrow derived macrophages (BMDM) were divided into control, lipopolysaccharide (LPS), UTI+LPS and UTI groups. TNF-α, TGF-β, IL-10, CD86, CD206 and MCP-1 expression were assessed by Western blot. The phagocytosis and migration of BMDM were detected. Pulmonary microvascular endothelial cells (PMVECs) were cultured with the conditioned medium (CM) from each group of BMDM above. Sprague-Dawley rats were divided into sham, cecal ligation and puncture (CLP), and UTI+CLP groups. Western blot and immunofluorescence were used to detected zonula occludens-1 (ZO-1), occludin and claudin-5 expression in PMVECs, as well as TNF-α, TGF-β, iNOS, CD86 and CD206 expression in lungs. Pulmonary capillary permeability was assessed by extravasated Evans blue, lung injury score (LIS), wet-to-dry weight ratio and electron microscope.Results: TNF-α and CD86 expression were increased in LPS-treated BMDM, but were reversed by UTI pretreatment. TGF-β, IL-10 and CD206 expression were the opposite. UTI markedly decreased phagocytosis and migration of LPS-treated BMDM. ZO-1, occludin and claudin-5 expression were markedly decreased in PMVECs of the CM-LPS group, but significantly increased in the CM-UTI+LPS group. TNF-α, iNOS and CD86 expression were increased in the lungs of CLP-rats but decreased with UTI pretreatment, while TGF-β and CD206 expression were the opposite. UTI markedly ameliorated the lung EB leakage, improved LIS, reduced the wet-to-dry ratio and revised the damaged TJs of PMVECs in CLP-rats.Conclusion: UTI effectively inhibits the conversion of M1 macrophage but increases M2, reduces the phagocytosis and migration, which helps to protect endothelia TJs and reduce pulmonary capillary permeability during sepsis.Keywords: ulinastatin, sepsis, macrophage, pulmonary capillary endothelial cells, tight junctions